Temporal changes in blood biomarkers associated with sleep apnoea severity: a retrospective cohort study in Finland - Hellen, Mira; Ruoranen, Toni; Toppila-Salmi, Sanna; Vasankari, Tuula; Kreivi, Hanna-Riikka; Mattila, Tiina; Ollila, Hanna M.; Strausz, Satu (BMJ PUBLISHING GROUP, 2025)
Introduction: Obstructive sleep apnoea (OSA) is a common sleep disorder associated with breathing interruptions during sleep, often leading to oxygen level drops and sleep disturbances. OSA is known to impact various physiological parameters, including haematological and lipid profiles. This study aims to investigate the effect of continuous positive airway pressure (CPAP) therapy on laboratory values in patients with OSA.
Methods: A retrospective study was conducted using data from Finland's largest hospital district, including 30 722 adult OSA patients treated between 2005 and 2020. A text search algorithm was implemented within the patient chart data to extract the apnoea-hypopnoea index (AHI) and the usage of CPAP therapy, along with identifying patients who had declined treatment. Haematological and metabolic laboratory values were collected 3 years before and after the first OSA diagnosis. Analysis of covariance was employed to compare parameter variations across severity levels, adjusted for age, sex and body mass index (BMI). T-test for repeated measurements was used to analyse the differences between data, 3 years prior and 3 years after the first OSA diagnosis.
Results: The study of 30 722 OSA patients showed varying severity levels: 14.8% mild, 32.6% moderate and 52.6% severe, with an average diagnosis age of 55.0 years and a mean BMI of 32.4. The most clinically significant changes were observed in lipid profile markers, with improvements in cholesterol and low-density lipoprotein (LDL) levels (p value<0.05), measured before CPAP treatment initiation and after the treatment began. Conversely, glucose levels increased during the follow-up period. Similarly, haematocrit and haemoglobin decreased significantly after initiation of the CPAP treatment. In sex-specific analyses, significant improvements in cholesterol and LDL levels were found in both sexes. Triglyceride levels improved in male patients, in contrast with female participants, whose triglyceride levels increased during the follow-up period.
Conclusions: CPAP therapy significantly improves cholesterol and LDL levels in both sexes and reduces haematocrit and haemoglobin levels. This study highlights the systemic effects of OSA and underscores the importance of evaluating haematological and lipid profiles in OSA management.